1981
DOI: 10.1152/ajpgi.1981.241.4.g300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spironolactone and amiloride on corticosteroid-induced changes in colonic function

Abstract: Mineralocorticoid and glucocorticoid effects on colonic electrolyte absorption were compared by examining the alterations caused by spironolactone and amiloride in corticosteroid-treated rats. Animals were treated for 3 days with deoxycorticosterone acetate (DOCA; 0.5 mg . 100 g-1 . day-1), methylprednisolone (MP; 3 or 0.5 mg . 100 g-1 . day), and spironolactone (14 mg . 100 g-1 . day-1 im) singly or in combination. On day 4, rats were anesthetized with pentobarbital sodium and perfused in vivo with Ringer-HCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…It is now well accepted that aldosterone stimulates active amiloride-sensitive sodium absorption and active potassium secretion in the distal colon of rat and rabbit (3)(4)(5). Glucocor- ticosteroids have similar, but not identical effects on electrolyte transport in the mammalian colon (1,(7)(8)(9)(10)(11)(12), and considerable uncertainty exists regarding the exact role of aldosterone and glucocorticoids in the regulation of colonic ion transport. The demonstration that both specific mineralocorticoid and glucocorticoid cytosolic receptors are present in the rat and rabbit colon is consistent with the interpretation that each cytosolic steroid receptor mediates specific ion transport processes (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now well accepted that aldosterone stimulates active amiloride-sensitive sodium absorption and active potassium secretion in the distal colon of rat and rabbit (3)(4)(5). Glucocor- ticosteroids have similar, but not identical effects on electrolyte transport in the mammalian colon (1,(7)(8)(9)(10)(11)(12), and considerable uncertainty exists regarding the exact role of aldosterone and glucocorticoids in the regulation of colonic ion transport. The demonstration that both specific mineralocorticoid and glucocorticoid cytosolic receptors are present in the rat and rabbit colon is consistent with the interpretation that each cytosolic steroid receptor mediates specific ion transport processes (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…However, dietary sodium depletion also affects electroneutral sodium and potassium absorption in the rat distal colon: electroneutral Na-Cl absorption is inhibited and electroneutral potassium absorption is stimulated (3,5). Recent studies with continuous infusion of aldosterone have confirmed that the changes in sodium and chloride transport observed in dietary sodium depletion are due to aldosterone (6); similar studies have not yet been performed for potassium transport. Synthetic glucocorticoids (e.g., dexamethasone, methylprednisolone) also produce substantial changes in both sodium and potassium movement in the mammalian distal colon (1,3,4,(7)(8)(9)(10)(11)(12). Although both glucocorticoid and aldosterone (i.e., mineralocorticoid) receptors have been identified in the cytosol of colonic epithelial cells (13)(14)(15)(16)(17), there has been considerable controversy whether separate and specific changes in ion transport are mediated by the activation of these glucocorticoid and mineralocorticoid receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In proximal colon, ileum, and jejunum, the major increase in sodium absorption and short-circuit current produced by glucocorticoids is amiloride resistant, a finding uncharacteristic for an aldosterone-induced response (2,8,36,49). In distal colon, amiloride-resistant transport may be induced with low doses or concentrations ofdexamethasone and amiloride-inhibitable transport induced at doses ofdexamethasone greater than the 10 nmol dose used in this study (2,3,5,7,8,17,18). Wills reported that the dose of dexamethasone required to produce 50% amiloride-sensitive short-circuit current in rat distal colon is 3 A/l00 g body wt per h (72 gg/I00 g body wt per d), a dose exceeding the highest dose (50 nmol) used in this study by 50% (8).…”
Section: Discussionmentioning
confidence: 70%
“…Subsequently, most of the in vivo and in vitro studies of glucocorticoid-induced colon transport have used amounts of glucocorticoids that could permit stimulation ofboth glucocorticoidand aldosterone-induced pathways (2)(3)(4)(5)(6)(7)(8)(9). Thus, the in vivo response of the colon to circulating physiologic levels of glucocorticoids has not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation